Hornschuchia mellosilvae (Annonaceae) a new species endemic to the Brazilian Atlantic Forest - Lopes, Jenifer De Carvalho; Vilela, Lucas; Johnson, David M. (Phytotaxa, 2021)
The Atlantic Forest is a biodiversity hotspot that includes different types of phytophysiognomies, mainly forests. Hornschuchia, Annonaceae, is one of its endemic genera. Eight Hornschuchia species are found in the tropical moist forest, three of them both occurring in tropical moist forest and tabuleiro forest, a semideciduous seasonal forest, one occurs in the coastal semideciduous seasonal forest and two inhabit the semideciduous seasonal forest and deciduous seasonal forest far from the coast in Bahia. Here we describe the twelfth species of Hornschuchia, which occurs in the Bahian semideciduous seasonal forest, and present a morphological description, illustration, distribution map and assessment of its conservation status.